The legal history of Transylvania (Academic Journal of Internal Affairs, 2018)
A brilliant present was granted for people interested in history, especially in Hungarian legal history, both for Hungarian law students in Romania and for other Hungarian speaking students or active lawyers with the book titled  The legal history of Transylvania, edited by  Emõd Veress, published by Forum Iuris of Cluj-Napoca in an extent of 592 pages. This book, intended to be used both as a scientific work and as a textbook, is the product of a collective work of seventeen authors, nine of them from Transylvania and eight Hungarian law scholars (from Transylvania: Zsolt Fenyvesi, Erwin Gáll, Hunor Kádár, Zsolt Kokoly, Tamás Nótári, Ádám Szabó, János Székely, Norbert Szeredai and Emőd Veress; and from Hungary: Andrea Domokos, Attila Horváth, Barna Mezei, László Nánási, Mária Homoki-Nagy, Károly Kisteleki, István Stipka and György Szabados.  Among the proof-readers was another Hungarian legal scholar: József Petrétei.) The authors listed above wrote one chapter each and they were compiled by the editor.
Keywords: legal; history; Transylvania